BELARUSIAN PROJECT “ASTROBLOKNOT” (ASTRONOMICAL NOTEBOOK) AND DATA MINING: RESULTS OBTAINED IN THE CONSTELLATION OF EQUULEUS - Sergey, Ivan; Dubrouski, Sergei; Baluk, Igor; Pobiacha, Alexander (Одеські астрономічні публікації, 2013)
Many photometric sky surveys are currently available on the open-access web-sources. The Northern Sky Variability Survey (NSVS), the All Sky Automated Survey 3 (ASAS-3) and the Catalina Real-Time Transient Survey (CRTS) are the most popular among them. In February 2013, Belarusian amateur astronomers made the decision to carry out a search for new variable stars using the CRTS dataset